The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2478/s11535-010-0119-9
|View full text |Cite
|
Sign up to set email alerts
|

Seeing through the lizard’s trick: do avian predators avoid autotomous tails?

Abstract: Counter-adaptations of predators towards their prey are a far less investigated phenomenon in predator-prey interactions. Caudal autotomy is generally considered an effective last-resort mechanism for evading predators. However, in victim-exploiter relationships, the efficacy of a strategy will obviously depend on the antagonist’s ability to counter it. In the logic of the predator-prey arms race, one would expect predators to develop attack strategies that minimize the chance of autotomy of the prey and damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…As the size of the receptive field involved in processing early motion signals in vertebrates is small, it is possible that the accuracy of attacks is affected by the eye gaze being directed to an apparently immobile anterior part of the prey containing striped patterns rather than global prey movement [ 40 ]. Moreover, it is known that predators target vital body parts such as the head or trunk to thwart prey escape [ 41 ], particularly in the case of lizards [ 27 , 28 , 42 ]. This was approximated in our experiments by instructing the volunteers to attack the anterior half of the moving prey.…”
Section: Discussionmentioning
confidence: 99%
“…As the size of the receptive field involved in processing early motion signals in vertebrates is small, it is possible that the accuracy of attacks is affected by the eye gaze being directed to an apparently immobile anterior part of the prey containing striped patterns rather than global prey movement [ 40 ]. Moreover, it is known that predators target vital body parts such as the head or trunk to thwart prey escape [ 41 ], particularly in the case of lizards [ 27 , 28 , 42 ]. This was approximated in our experiments by instructing the volunteers to attack the anterior half of the moving prey.…”
Section: Discussionmentioning
confidence: 99%
“…Caudal autotomy has been little studied in rodents, in comparison with lizards (Cooper et al 2004, Bateman and Fleming 2009). In some lizard species, studies have shown that some predator species do not catch their prey by the tail, but focus on other body parts such as the area around the head in a context of predator–prey arms race (Vervust et al 2011). This could also be the case for predators of deer mice and red‐backed voles.…”
Section: Methodsmentioning
confidence: 99%
“…A relatively simple experiment with undifferentiated clay models of the lizard Podarcis sicula (Lacertidae) on small islets in the Mediterranean revealed the predatory behaviour of the primary predators, yellow‐legged gulls Larus michahellis , for these sites (Vervust, Van Loy & Van Damme, ). The authors recorded more attacks aimed at the heads of their models (Vervust et al ., ), which would translate to potentially fatal attacks in live lizards.…”
Section: The Questionsmentioning
confidence: 99%
“…A relatively simple experiment with undifferentiated clay models of the lizard Podarcis sicula (Lacertidae) on small islets in the Mediterranean revealed the predatory behaviour of the primary predators, yellow‐legged gulls Larus michahellis , for these sites (Vervust, Van Loy & Van Damme, ). The authors recorded more attacks aimed at the heads of their models (Vervust et al ., ), which would translate to potentially fatal attacks in live lizards. Such behaviour by predators is likely to be the selective pressure that results in many species of lizard having brightly coloured tails (Vitt & Cooper, ; Castilla et al ., ; Bateman et al ., ) or behaviour such as tail waving (Cooper, ; Telemeco, Baird & Shine, ) that directs attacks towards autotomizable tails (Bateman & Fleming, ), and may also select for longer tails (Fleming, Valentine & Bateman, ).…”
Section: The Questionsmentioning
confidence: 99%